İlaç firmalarında muhasebe sistemi ve maliyet yönetimi - Seyhan, Çiğdem (My University, 2001)
Bu çalışmanın konusu ilaç firmalarında muhasebe sistemi ve maaliyet yönetimidir. Konuya öncelikle Türk ilaç sektörü üzerine genel bir değerlendirme yapılarak başlanmıştır. Çalışmayı daha somut bir temele dayandırmak açısından konuları anlatırken Merck Sharp and Dohme İlaç firması örnek alınmıştır. Ve bu bağlamda henüz beş senedir Türkiye'de faaliyette bulunan firma hakkında genel bir bilgi verilmiştir. Dünya ilaç sektöründe en büyük firmalardan biri olan Merck ülkemizde sektörde dokuzuncu sıradadır. Şirket Türkiye pazarındaki payını hızla artırmaktadır. Çalışmanın ikinci bölümünde muhasebe organizasyon yapısı üretim maliyet yapısı ile anlatılmaya başlanmıştır.Bu başlık altında hammadde giderleri, fason üretim giderleri , ruhsatlandırma ve fiyat başvurusu (onay) incelenmiştir. İthalat maliyetleri, dağıtım maliyetleri, pazarlama giderleri ve ilaç tanıtım giderleri anlatılırken mümkün olduğunca konularla paralel bir şekilde kullanılan belgelere ilişkin örnekler verilmeye çalışılmıştır.İkinci bölümün sonunda genel yönetim giderleri, stok yapısı, envanter ve kar zararın oluşumuna yer verilmiştir. Sonuç ve kaynaklar bölümünün ardından yer alan ekler bölümünde çalışmanın ilgili bölümlerinde anlatılan konulara ait ve firmada iş akışı içerisinde kullanılan belgeler yer almaktadır.

The subject of this study is the accounting system and cost management in pharmaceutical manufacturer firms. The study starts with a general overview of Turkish Pharmaceutical Industry. For the sake of a concrete base to build the study upon, we take Merck Sharp & Dohme as a model pharmaceutical manufacturer. General information about the structure of the firm, which has been operating in Turkey for just five years, is also included. In the 2nd part, accounting organization structure is described starting with the production cost structure. While examining the cost structure, its basic topics like raw material inputs, intermediary production expenses, licensing, pricing and price application (approval) are also discussed in detail. In accordance with the 5th item of Annex-8 of the 'Partnership Committee Decree' numbered 1/ 95 within the Customs Union Treaty between our country and the European Committee, dated March 6,1995; Turkey would apply patent protection to its pharmaceutical manufacturing methods and products by January 01, 1999. The affect of this application over the industry is also discussed. While mentioning about import, distribution, marketing and advertisement expenses, parallel with the subjects, some samples of the used documents are given when possible. Especially, based upon a marketing approach that is specific to the pharmaceutical industry, the procedures that must be applied during these marketing activities and the written forms that are the basis of these procedures are also included. At the end of the 2nd part, general management expenses, stock structure, inventory, and the profit and loss status of the firm are discussed. In the appendices part, which comes after the conclusion and references, you would find some documents that are used in the workflow of the firm or that belongs to the related topics of the study.
Keywords: Maliyet muhasebesi; MUHASEBE-